2016
DOI: 10.18632/oncotarget.10143
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 9 inhibits hepatocellular carcinoma through up-regulating FOXO1 expression

Abstract: Aquaporin 9 (AQP9) is the main aquaglyceroporin in the liver. Few studies have been performed regarding the role of AQP9 in liver cancer. Here we report AQP9 expression and function in liver cancer. We found that AQP9 mRNA and protein levels were reduced in human hepatocellular cancer compared to the para-tumor normal liver tissues. Human hepatoma cell line SMMC7721 expressed low basal levels of AQP9. When AQP9 was overexpressed in SMMC7721 cell line, cell proliferation was inhibited due to cell cycle arrest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…This was also demonstrated for AQP9, as inward water fluxes weakened membranecytoskeleton anchorage and increased filopodia formation (15,20). Interestingly, despite these functional properties of AQP9, which would suggest an oncogenic effect, AQP9 expression has been found to suppress cancer cell progression (10,18,50). In this study we found that AQP5-expressing MDCK cells displayed unchanged filopodia formation but more dynamic lamellipodia compared with control cells.…”
Section: C658supporting
confidence: 61%
See 1 more Smart Citation
“…This was also demonstrated for AQP9, as inward water fluxes weakened membranecytoskeleton anchorage and increased filopodia formation (15,20). Interestingly, despite these functional properties of AQP9, which would suggest an oncogenic effect, AQP9 expression has been found to suppress cancer cell progression (10,18,50). In this study we found that AQP5-expressing MDCK cells displayed unchanged filopodia formation but more dynamic lamellipodia compared with control cells.…”
Section: C658supporting
confidence: 61%
“…These studies showed that AQP9 expression stimulated cellular filopodia and protrusion formation, structures that enable cell migration. Surprisingly, in contrast to cancer cells expressing AQP5, overexpression of AQP9 in cancer cells decreased EMT and improved cancer treatment (10,18,50).…”
Section: Introductionmentioning
confidence: 99%
“…FOXO1 is a member of the forkhead box O (FOXO) family, which a series of recent studies have demonstrated plays an important role in several intracellular functions, including autophagy [7], cell cycle [8], apoptosis [9], and tumor suppression [10]. Various experiments pointed out that post-translational modifications regulated FOXO1 transcriptional activities and modulated FOXO1 protein stability, DNA binding activity, protein-protein interactions, and subcellular localization, all of which are involved in regulating autophagic flux [7, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Increases or decreases in AQP9 expression have been detected in different tumor types. AQP9 is significantly enhanced in prostate cancer tissues than that in adjacent cancer tissues (14); however, AQP9 levels are reduced in human hepatocellular carcinoma compared with the paratumoral normal liver tissues (15). The present study demonstrated that AQP9 was expressed in astrocytoma cells, indicating that AQP9 may be involved in astrocytoma cell progression.…”
Section: Discussionmentioning
confidence: 48%